2002
DOI: 10.1128/aac.46.7.2257-2261.2002
|View full text |Cite
|
Sign up to set email alerts
|

Novel Class 1 Integron (InS21) Carrying bla CTX-M-2 in Salmonella enterica Serovar Infantis

Abstract: The genetic organization of the region coding for CTX-M-2 in Salmonella enterica serovar Infantis was determined by PCR mapping. This gene seems to have been mobilized from the Kluyvera ascorbata chromosome to a complex sulI-type integron, similar to In6 and In7

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
68
1
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(73 citation statements)
references
References 19 publications
3
68
1
1
Order By: Relevance
“…Since ESBL genes reside on plasmids or integrons, they have the potential to spread to other organisms [13,14]. And indeed, in this study, we successfully demonstrated the transfer of resistance by conjugation, suggesting that blaCTX-M-15 is located on a self-transferable plasmid.…”
supporting
confidence: 53%
See 1 more Smart Citation
“…Since ESBL genes reside on plasmids or integrons, they have the potential to spread to other organisms [13,14]. And indeed, in this study, we successfully demonstrated the transfer of resistance by conjugation, suggesting that blaCTX-M-15 is located on a self-transferable plasmid.…”
supporting
confidence: 53%
“…Among the six groups of CTX-M enzymes, the CTX-M-1, -2, and -9 groups have been reported in serotypes Typhimurium, Enteritidis, Virchow, Kentucky, and Kedougou [5,[13][14][15]. CTX-M-15 ESBL was first reported in E. coli, K. pneumoniae, and Enterobacter aerogenes isolates in [2000][2001] in India [16].…”
Section: Discussionmentioning
confidence: 99%
“…En estos ensayos se utilizaron como cepas de control E. coli LMM36-ULA (chuA+ y yjaA +) y E. coli LMM32-ULA (TspE4.C2 +). Detección y secuenciación de los genes bla TEM , bla SHV y bla CTX-M En la detección de los genes codificantes para TEM, SHV y CTX-M en las cepas estudiadas, se utilizaron los iniciadores señalados en el cuadro 1 y las condiciones de amplificación descritas en estudios previos (17)(18)(19)(20).…”
Section: Detección De Los Grupos Filogenéticosunclassified
“…Among the six groups of CTX-M enzymes (1), the CTX-M-1, -2, and -9 groups have been reported in serovars Typhimurium, Virchow, Enteritidis, Kentucky, Infantis, and Oranienburg (1,3,5,12,19). However, to the best of our knowledge this is the first report of a CTX-M-14 enzymeproducing Salmonella serovar London, which suggests a gradual spread of this resistance to various serovars of Salmonella.…”
mentioning
confidence: 91%